Gradient of strength properties in stainless steel wire after cryogenic cooling - Volokitina, Irina; Panin, Evgeny; Zhumanazarova, Gulnura; Gelmanova, Zoya (Edelweiss Applied Science and Technology, 2026)
This article considers an advanced technology used for processing stainless steel wire, namely cryogenic drawing. The essence of the developed technology lies in the fact that, prior to the beginning of the drawing process, the wire undergoes preliminary heat treatment, which includes quenching at a high temperature reaching 1050 °C. After this stage, conventional drawing is performed, followed by a stage of cryogenic cooling. This process is carried out after each deformation cycle, which makes it possible to significantly modify the properties of the material. A distinctive feature of this study is the use of intermediate heating of the wire to room temperature between deformation cycles. The results of laboratory experiments conducted within this work clearly demonstrate that cryogenic treatment significantly improves the mechanical characteristics of the wire compared with conventional drawing. The application of intermediate heating leads to the formation of a unique gradient microstructure consisting of martensite and austenite. A nanostructured martensitic layer with a grain size of approximately 0.5 µm is formed on the surface of the wire. This grain size gradually increases toward the center of the wire, creating gradient material properties. The research results, presented in the form of detailed tables, graphs showing the dependence of mechanical properties on the number of deformation cycles, and high-resolution micrographs, clearly demonstrate significant differences in the microstructure and properties of the obtained wire.